Communication Style in the Salesperson-Customer Dyad - Williams, Kaylene C.; Spiro, Rosann L. (Journal of Marketing Research, 1985)
The authors report a study designed to evaluate the use of communication style by salespeople and their customers. Using a paradigm suggested by Sheth in which the communication styles of customers and salespeople are categorized as task oriented, interaction oriented, or self oriented, they assess whether communication styles are related to sales. They first develop scales to measure these styles and then test whether the styles affect the sales outcome. The results suggest that communication styles are a determinant of the success of the sales interaction.